Kekuatan Hukum Akta Jual Beli Yang Tidak Mengikutsertakan Seluruh Ahli Waris Sebagai Para Pihak - Syahputra, M Afit; Dewi, R. Ismala (Jurnal Ilmiah Mandala Education (JIME), 2022)
Land Deed Making Officials (PPAT) are often Public Officials who intentionally or unintentionally act negligently in making the deed of sale and purchase. One of them is not involving all the heirs as parties. It can cause losses to interested parties on the object of the sale and purchase deed. For this reason, it is necessary to do research on the power of law, by analyzing the Decision of the Ngawi District Court 14/ /Pdt.G./2019/PN Ngw, which there are two problems to be raised, namely the legal power of the sale and purchase deed which does not include all heirs as parties and the responsibility of PPAT to make a deed of sale and purchase without the permission of all heirs as parties. To answer these problems, research is carried out using normative legal research methods. The results of the study showed that the Deed of Sale and Purchase which did not include all heirs was null and void. Therefore, it is recommended that a PPAT must comprehensively ensure that all heirs participate in the making of the Deed of Sale and Purchase.